Prevalence and factors associated with intimate partner violence among postpartum women attending government primary health care clinics in Malaysia - Chan, Ying Ying; Rosman, Azriman; Ahmad, Noor Ani; Mohamad Kasim, Noraida; Abd Razak, Mohamad Aznuddin; Omar, Maisarah; Abdul Aziz, Fazly Azry; Awaluddin, S. Maria; Yusof, Muslimah; Jamaluddin, Rasidah; Ab Wahab, Nor’Ain; Md Rosli, Najwa Hanim (Springer New York LLC, 2019)
Intimate partner violence (IPV) is an important gender-based, social, and public health problem that affects women worldwide, including women who are pregnant or have recently given birth. Studies have shown that violence against women often increases during pregnancy and the postpartum period. This study aims to examine lifetime and past-year prevalence of IPVamong postpartum women in Malaysia, and to determine the socio-demographic as well as husband’s/partner’s behavioral factors associated with IPV exposure. This is a nationwide, cross-sectional and clinic-based study involving a total of 5727 women at 6 to 16 weeks postpartum, who attended randomly selected government health clinics between July to November 2016. Face-to-face interviews were conducted by trained female enumerators based on a pre-validated structured questionnaire, using mobile devices as data collection tools. Chisquared tests and multivariable logistic regressions were used to investigate selected factors associated with IPVexposure. The lifetime and past-year prevalence of any form of IPV among postpartum women were 4.94% (95% CI [3.81,6.39]) and 2.42% (95% CI [1.74,3.35]) respectively, with the highest prevalence being emotional violence, followed by physical and sexual violence. Multivariable analysis showed that husband’s/partner’s behaviors, such as frequent alcohol use, drug use, fighting habits and controlling behaviour were significantly associated with both lifetime and past-year IPV (all p < 0.001 for past-year IPV). These findings suggest that prevention and intervention strategies for IPV should consider the prevention of substance use and reducing controlling behaviors by husband/partner, as well as raising awareness to build healthy relationships through education.